ANALISIS HUBUNGAN ANTARA LITERASI KEUANGAN DENGAN KEMAMPUAN MATEMATIS - Phety, Debora Tri Oktarina; Asri, Yoana Nurul; Alti, Rahmi Mudia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine the relationship between financial literacy and students' mathematical abilities. Financial literacy is divided into 5 categories, namely general knowledge, financial management, credit management, savings and investment, and risk management. The category of understanding general knowledge about finance obtained results of 82%, financial management ability by 78%, credit management by 21%, savings and investment by 67%, and risk management by 42%. Of the five categories of financial literacy, only one category is classified as high understanding (>79%) namely general knowledge about finance. With an average understanding of 58% and classified as low to enough. Then from the 27 statement items, the test was carried out again through 20 statement items. After conducting a survey on the level of financial literacy, then a survey related to the mathematical ability of the respondents was carried out. The distribution of the questions consists of 20 questions which are divided into 11 types of questions. From this math test, the overall score was relatively low. As many as 42% can answer correctly above the average (>70). So that from the two test instruments, the results obtained a significant and positive correlation between financial literacy and mathematical ability.